Gender, Criminalization and Prohibitionism: the incarceration of women in Costa Rica and Brazil - Monteiro Garcia, Renata; Gonçalves da Silva, Alexia Carolina; Trindade Silva Borges, Jeferson; Medeiros dos Santos Cavalcante, Rayssa (Revista de Ciências Sociais, 2023)
This study aims to compare and discuss the relationship between women's imprisonment and the War on Drugs policy in Brazil and Costa Rica. Therefore, being an exploratory and qualitative research, two different types of data collection procedures were used, namely: a bibliographic research with survey of scientific articles, theses and dissertations and a documentary research on local legislation, government reports and statistical reports. The main results demonstrate the urgency of critical discussions on criminal policy in which gender is a category of analysis. It is concluded that the violations of the rights of incarcerated women happen in a historical and continuous way, but they will be more ostensible from a complex relationship between these violations and international policies of penalization and prohibition of Drugs.